2021
DOI: 10.1038/s41467-021-24764-8
|View full text |Cite
|
Sign up to set email alerts
|

Valley-selective optical Stark effect of exciton-polaritons in a monolayer semiconductor

Abstract: Selective breaking of degenerate energy levels is a well-known tool for coherent manipulation of spin states. Though most simply achieved with magnetic fields, polarization-sensitive optical methods provide high-speed alternatives. Exploiting the optical selection rules of transition metal dichalcogenide monolayers, the optical Stark effect allows for ultrafast manipulation of valley-coherent excitons. Compared to excitons in these materials, microcavity exciton-polaritons offer a promising alternative for val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 38 publications
(67 reference statements)
0
18
0
Order By: Relevance
“…S23 suggest that PHET is not a prominent process in our results. Moreover, the possible influences from the valley-selective resonant optical Stark effect in TMD-based plexcitons can also be eliminated, as the pump and probe beams are cross-circularly polarized 68 , 69 .…”
Section: Discussionmentioning
confidence: 99%
“…S23 suggest that PHET is not a prominent process in our results. Moreover, the possible influences from the valley-selective resonant optical Stark effect in TMD-based plexcitons can also be eliminated, as the pump and probe beams are cross-circularly polarized 68 , 69 .…”
Section: Discussionmentioning
confidence: 99%
“…Another important result has been obtained by LaMountain et al [353] that demonstrated the valley-selective optical Stark effect in a WS 2 monolayer planar microcavity at room temperature. The authors used an ultrafast pump-probe technique in which the pump is detuned ≈520 meV (redshifted) with respect to the polariton modes, and the probe is used to monitor the energy shift of both UP and LP branches.…”
Section: Valley Polarization In Tmd Microcavitiesmentioning
confidence: 70%
“…The pump has circular polarization, σ, while the probe is switched in either σ or σ−, as shown in Fig. 11 valley-selective shift of highly detuned polaritons at room temperature [353] .…”
Section: Valley Polarization In Tmd Microcavitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Laser-field manipulation of electronic band structure is at the frontier of quantum-materials research [1]. In particular, monolayer transition-metal dichalcogenides (TMDs) exhibit remarkable excitonic properties as a result of their reduced dimensionality [2], and recent spectroscopic studies have shown their promising potential toward novel optoelectronic devices [4][5][6][7][8][9][10][11][12][13]. One of the common approaches is to coherently drive the interband transition by a near-resonant visible pulse and induce an AC-Stark shift to the exciton resonance [4,5].…”
mentioning
confidence: 99%